Car rollover collision with pit corner - Viba, Janis; Liberts, Gundars; Gonca, Vladimirs (Transport, 2009)
The paper presents a theory of body collision with pit corner. The theory can be successfully applied in approaching tasks coping with the orientation of details in technological processes and control systems, the motion of elements in mechanisms having a gap, collisions in motion of different sport objects, the analysis of car accidents etc. The applied theory deals with car motion after collision with a specific obstacle i.e. pit corner. The study is based on linear and angular momentum theorems and two restitution coefficients of normal impulse from both sides of the obstacle. The obtained results can be used for assessing road accidents in case of car collision with one or more obstacles. The object of contact may involve hitting a plane foundation, the ditch and edging of a highway or a rock in the field.First published online: 27 Oct 2010